CHILDHOOD SOCIAL SKILLS AND ATTACHMENT STYLES: A SYSTEMATIC REVIEW - Ninda Falah Yuniar (OPTIMA: Journal Of Guidance and Counseling, 2021)
Attachment is the first and most crucial relationship that children have with their caregivers (often the mother but not necessarily); the built relationship will last long enough and provide a sense of security even though the attachment figure is not visible in the child's view. Examined the impact of attachment and its effect on social skills. Consequently, this study systematically reviews evidence on attachment and social skills. A total of 35 articles published between 2001 and 2020 met the criteria after searching in the following databases: sage journal, springer link, thesis database, science direct, hazing, researchgate, Google, Google Scholar. Cambridge. The findings suggest a positive relationship between safe and unsafe attachment (anxiety and avoidance) and social skills. The findings show that safe attachment will provide self-confidence, responsiveness, shows that children's social competence can relate well to teachers and peers at school and in the community. The unsafe attachment will hurt the child. Children arenot confident and less good at responding to their environment or lack social skills.